IMPLEMENTASI PRINSIP DESAIN ARSITEKTUR BIOKLIMATIK PADA BANGUNAN PERPUSTAKAAN DI KLATEN - Hajar Kusuma Cahyaningrum; Hardiyati Hardiyati; Rachmadi Nugroho (ARSITEKTURA, 2017)
AbstractAlong with the development of science, the more advanced information and technology are invited in which people are required to always be up to date with the development of existing information. Science and information technology are closely related to the education in which the needs for growing information are considered less achieved by formal education. Therefore, public facilities as educational tools to obtain science and information outside the formal education need to be improved.  Library is required to provide a better and appropriate information services to attract reader from various side. The planned library is public buildings which provide information with various supporting facilities to gain knowledge for readers. The Library being discussed here is not merely about the book but there are many latest technologies as supporting information needs.  Using bioclimatic architecture, the library building is expected to be a convenient educational facility considering the phenomena and the tropical climate of Klaten City to obtain building criteria based on the basic principles of bioclimatic architecture.   Keywords : science, information technology, education, library, public building, bioclimatic, bioclimatic architecture.